Broken harmony: Shakespeare and the politics of music - Ortiz, Joseph M. (Cornell University Press, 2011)
Titus Andronicus and the production of musical meaning -- "Her speech is nothing" : mad speech and the female musician -- Teaching music : the rule of allegory -- Impolitic noise : resisting Orpheus from Julius Caesar to The tempest -- Shakespeare's idolatry : psalms and hornpipes in The winter's tale -- The reforming of reformation : Milton's A maske